2015
DOI: 10.1590/0037-8682-0023-2015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of group A rotavirus before and after the introduction of vaccines in Brazil

Abstract: Introduction: In this study, the molecular characteristics of group A rotavirus (RVA) were compared in samples obtained before and after RVA vaccine-introduction in Brazil. Methods: Eighty samples were screened for the presence of RVA. Positive samples were molecularly analyzed. Results: RVA positivity was 16.9%, with a predominance of G2P [4]. Periods: pre-vaccination: predominance of IId (G1), IId (G2) lineages, and I1 and E1 genotypes; post-vaccination: predominance of Ib (G1), IIa, and IIc (G2) lineages an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Such a scenario was observed in Japan where, a G8P[8] RVA strain appeared to emerge and was found in up to 66% (53/80) of children with acute gastroenteritis disease attending one pediatric clinic in Shizuoka Prefecture in February – July 2017 10 . Similarly, the predominance of non-vaccine type G2P[4] strains was observed in Rotarix® vaccinated populations of Belgium 11 and Brazil 12 . Although the rise was not linked to pressure induced by the vaccine, concerns still remain on the overall effect of the vaccine on circulating vaccine heterotypic strains.…”
Section: Introductionmentioning
confidence: 81%
“…Such a scenario was observed in Japan where, a G8P[8] RVA strain appeared to emerge and was found in up to 66% (53/80) of children with acute gastroenteritis disease attending one pediatric clinic in Shizuoka Prefecture in February – July 2017 10 . Similarly, the predominance of non-vaccine type G2P[4] strains was observed in Rotarix® vaccinated populations of Belgium 11 and Brazil 12 . Although the rise was not linked to pressure induced by the vaccine, concerns still remain on the overall effect of the vaccine on circulating vaccine heterotypic strains.…”
Section: Introductionmentioning
confidence: 81%
“…Worldwide G1 and P [8] have been the predominant genotypes (Santos & Hoshino, 2005), being replaced at regular intervals, especially by G2 and P [4] ( Dóró et al, 2014), as well as other emerging genotypes such as G5 and G9 (Santos & Hoshino, 2005). Many studies of the genotypic profile of RVA, in the Brazilian Mid-West, have been conducted since 1986, detecting the occurrence of distinct G and P genotypes with changes over time, notably G1P [8], G2P [4] and G9P [8] (Cardoso et al 2000, Souza et al 2003, Costa et al 2004, Andreasi et al 2007, Munford et al 2009, Borges et al 2011, Almeida et al 2015.…”
mentioning
confidence: 99%
“…Studies conducted in the Brazilian Mid-West have shown a temporal variation in the predominance of certain G and P genotypes, characterizing the occurrence of an antigenic shift (Cardoso et al, 2000, Souza et al, 2003, Costa et al, 2004, Andreasi et al, 2007, Munford et al, 2009, Borges et al, 2011, Almeida et al, 2015.…”
mentioning
confidence: 99%
See 2 more Smart Citations